ENT 530 Case Study / Izham Hajar ... [et al.] - Hajar, Izham; Abdul Rahim, Fatin Liyana; Kudang, Veronicca Babra Monna; Mohd Zaidi, Fatin Syafiqah (2018)
This report is all about one of company that register under Small Medium Enterprise (SME). The existence of this Small and Medium Enterprise has provided and opened a very wide range of jobs especially to low income rural populations. This is because there are many business opportunities in various sectors that can be explored in SME. The Jebat Catering is one of company that been register under SME that help them to operate their business. The important component of the Jebat Catering is how they start their business from nothing until they now have their own catering. The owner learning from the bottom how to conduct a business and he experience a lot of things. The management team in this company is being handle by the owner himself.